Jovens com deficiência : estudo de percursos de participação social no município de São Carlos, SP - Ferreira, Natasha Reis (2017)
Youth, period of transition to adulthood, range from 15 to 29 years. About 6 million young Brazilians have at least one disability, and even after promulgating policies focused primarily on education, their levels of education and participation in work is lower than compared to people without disabilities. In this way, it is important to establish policies, programs and actions to guarantee their rights to social participation. The study's purpose was identify the opportunities and barriers for the social participation of young people with disabilities disengaged from school, by dropping out or completing a course, and hypothesized that these opportunities are scarce, especially after disengaged. It's a qualitative study, which included documentary research on the actions aimed at the social participation of young people, held in secretariats of the city of São Carlos, interviews and recording of daily life by young people with disabilities disengaged from regular school between 2005 and 2010. The young people were found through the Municipal Council of the Person with Disabilities of the municipality and by appointment of their peers, being contacted in two stages. In the interview, the questions dealt with daily and social participation activities (work, study, leisure), being carried out in the homes, work or public space with 4 men interviewed. The second stage consisted of the participants daily knowledge through photographs taken by the interviewees based on the photovoice method. With the survey of actions, a response was obtained from six of the nine municipal secretariats, in which the Secretariat of Labor, Employment and Income and the Person with Disabilities and Reduced Mobility presented actions aimed at the general public. There were few specific actions for young people, especially those with disabilities. In order to understand the possible social participation paths in the municipality, maps were created with registration of the opportunities (work, leisure, elementary and secondary education, health units, collective transport, among other elements), also indicating the residence region of the participants. The speech of three interviewees indicated that the negative school experiences, besides marking the school life, were decisive in the trajectories of participation. The hypothesis that the disengagement from the school environment influences social participation can be confirmed by a respondent. The information from the maps, speeches and registers confirm the fact that the social participation of young people with disabilities is hampered by the greater concentration of opportunities in the central region of the municipality as by perceived obstacles in access and accessibility.